Mineral Acquisition from Clay by Budongo Forest Chimpanzees - Reynolds, Vernon; Lloyd, Andrew W.; English, Christopher J.; Lyons, Peter; Dodd, Howard; Hobaiter, Catherine; Newton-Fisher, Nicholas; Mullins, Caroline; Lamon, Noemie; Schel, Anne Marijke; Fallon, Brittany (PLOS ONE, 2015)
Chimpanzees of the Sonso community, Budongo Forest, Uganda were observed eating clay and drinking clay-water from waterholes. We show that clay, clay-rich water, and clay obtained with leaf sponges, provide a range of minerals in different concentrations. The presence of aluminium in the clay consumed indicates that it takes the form of kaolinite. We discuss the contribution of clay geophagy to the mineral intake of the Sonso chimpanzees and show that clay eaten using leaf sponges is particularly rich in minerals. We show that termite mound soil, also regularly consumed, is rich in minerals. We discuss the frequency of clay and termite soil geophagy in the context of the disappearance from Budongo Forest of a formerly rich source of minerals, the decaying pith of Raphia farinifera palms.